Веселый прогульщик: повесть / А. Б. Кораблев ; худож. В. Щербаков - Кораблев Артем Борисович (Черный котенок, 2000)
Экземпляры: аб. (2000) / Инвентарный номер: 42167 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: К 66 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44